Structural exploration of cannabinoid receptors using computational methods - Murali, Lahari (2020)
Cannabinoid receptors (CB1 and CB2) are signalling proteins which belong to the largest family of transmembrane proteins called G protein-coupled receptors (GPCRs). Since their discovery, they have been widely studied for the notable pharmacological influences exerted by their interaction with cannabinoids and are hence viewed as druggable targets for a number of diseases. Along with their endogenous ligands and the metabolic enzymes that affect the bioavailability of endogenous cannabinoids, they form the endocannabinoid system. The discovery of crystal structures of CB1 and CB2 in recent years has relayed critical information regarding the conformation of the receptors in active and inactive states, and their binding pocket interactions. Though being invaluable sources of information, rigid crystal structures cannot completely rationalise structure-activity relationship for all classes of ligands that interact with the receptors. The work reported herein describes the exploration of the structures of CB1 and CB2 receptors via computational tools such as molecular modelling, docking, and molecular dynamics simulation. Accordingly, significant variations in the conformations of CB1 and CB2 in different states of activation were studied. It was observed that transmembrane helices 1,3,6 and 7 influence the structural features of both receptors at different states. In recent years, many ligands that are not classified as cannabinoids have been shown to influence the endocannabinoid system. In this regard, the work presented here also analyses the interaction of non-cannabinoid ligands at CB1 and CB2. In this regard, a select group of commonly used drugs were tested against CB1 and CB2 using [35S]GTPγS binding assay for agonist activity. Furthermore, non-cannabinoids that have been reported to show activity at CB1 and CB2 were docked to models of the receptors to decipher their binding mode. It was found that the binding mode depends on the binding pocket surface area and is stereoisomer specific. In general, the work documented herein provides an insight into the structural complexities of these receptors for the cannabinoid research community.